Your Computer is Already A Distributed System. Why Isn't Your OS? - Baumann, Andrew; Peter, Simon; Schüpbach, Adrian; Singhania, Akhilesh; Roscoe, Timothy; Barham, Paul; Isaacs, Rebecca (12th Workshop on Hot Topics in Operating Systems, 2009)
We argue that a new OS for a multicore machine should be designed ground-up as a distributed system, using concepts from that ﬁeld. Modern hardware resembles a networked system even more than past large multiprocessors: in addition to familiar latency eﬀects, it exhibits node heterogeneity and dynamic membership changes. Cache coherence protocols encourage OS designers to selectively ignore this, except for limited performance reasons. Commodity OS designs have mostly assumed ﬁxed, uniform CPU architectures and memory systems.